Support For The Comprehensive School Health Model To Increase Reproductive Health Knowledge Of Elementary School Children As A Primary Prevention Effort - F. N. Putriningtyas, Ivony; Asmi Sulasri, Nur; Elan Mnsen, Reflin (Jurnal Ilmiah Kesehatan, 2023)
The research explores the impact of the Comprehensive School Health model on enhancing the reproductive health knowledge of primary school children as a primary prevention effort. In an era of rapid social and technological changes, early-age reproductive health awareness is crucial. This study aims to evaluate the effectiveness of the Comprehensive School Health model in improving the reproductive health knowledge of primary school children. The purpose of this research is to assess whether the Comprehensive School Health model significantly enhances the reproductive health knowledge of primary school children. It seeks to determine if this approach can be a viable strategy for primary prevention in the field of reproductive health. The study employs a pre-experimental design with a One Group Pretest-Posttest Design. Data was collected through observations, interviews, and documentation. The sample consists of sixth-grade students from an elementary school in Sorong District, selected using total sampling. Statistical analysis included Wilcoxon tests and rank biserial correlation. The results indicate a significant improvement in the reproductive health knowledge of primary school children following the intervention. The Wilcoxon test showed a p-value of <0.001, and the mean difference was -35.0, signifying a substantial increase in knowledge. The effect size was 1.62, indicating a significant impact, and a strong negative rank biserial correlation of -1.00 revealed a robust correlation between the intervention and knowledge improvement. This study concludes that the Comprehensive School Health model is effective in significantly enhancing the reproductive health knowledge of primary school children, with a substantial effect size and a strong correlation between the intervention and knowledge improvement. These findings emphasize the importance of early-age reproductive health education and highlight the potential of this model as an effective strategy for primary prevention in the field of reproductive health.